Essence and existence of singular things, or the univocity of being as a prolegomenon of the doctrine of Spinozian temporality - Sibilia, Guillermo (Pensamiento. Revista de Investigación e Información Filosófica, 2025)
The first part of Spinoza's Ethics has as one of its objectives to show that the infinite being (God sive sustancia), in the infinity of his orders of existence (attributes) and according to the infinite modalities of his existence (infinite modes), is always present in all the finite modalities of his potency. Now, when we turn our attention to these effects, more precisely to the finite modes, Spinozian ontology opens itself to difficult questions, which we are interested in addressing in this article: how do the finite modes arise and how should we think of the relation between their essence and their existence? How does Spinoza conceive the formal essence and the actual essence of these modes? The aim of this article is to answer these questions and to give a possible interpretation of the relation between the essence and the existence of finite singular things, which serves as a prolegomenon to his theory of temporality.
Keywords: ontology; essence; existence; finiteness